Environment and natural resource management in Bangladesh - Sadeque, S. Zahir (Dhaka : Bangladesh Sociological Association, 1992)
Environment Management
Bibliography : p. 192-196
1995-05-16
Keywords: Enviornment management; Natural resources; Bangladesh